Deviations from fundamental value and future closed-end country fund returns - Berggrun, Luis; Cardona, Emilio; Lizarzaburu, Edmundo (Universidad ESAN. ESAN Ediciones, 2021)
Purpose. This article examines whether deviations from fundamental value or closed-end country fund's discounts or premiums forecast future share price returns or net asset returns. Design/methodology/approach. The main empirical (econometric) tool is a vector autoregressive (VAR) model. The authors model share price returns and net asset returns as a function of their lagged values, the discounts or premiums, and a control variable for local market returns. The authors also conduct Dickey Fuller and Granger causality tests as well as impulse response functions. Findings. It was found that deviations from fundamental value do predict share price returns. This predictability is contrary to weak-form market efficiency. Premiums or discounts predict net asset returns but weakly. Originality/value. The findings point to the idea that the closed-end fund market is somewhat predictable and inefficient (in its weak form) since the market appears to be able to anticipate a fund's future returns using information contained in the premiums (or discounts). In particular, the market has the ability to anticipate future behaviour because growing premiums forecast declining share price returns for one or two periods ahead.

Propósito: Este artículo examina si las desviaciones del valor fundamental o los descuentos o primas de los fondos nacionales de tipo cerrado pronostican los rendimientos futuros del precio de las acciones o los rendimientos netos de los activos. Diseño/metodología/enfoque: La principal herramienta empírica (econométrica) es un modelo vectorial autorregresivo (VAR). Los autores modelan los rendimientos de los precios de las acciones y los rendimientos de los activos netos en función de sus valores rezagados, los descuentos o primas y una variable de control para los rendimientos del mercado local. Los autores también realizan pruebas de causalidad de Dickey Fuller y Granger, así como funciones de respuesta al impulso. Hallazgos: Se encontró que las desviaciones del valor fundamental predicen la rentabilidad del precio de las acciones. Esta previsibilidad es contraria a la eficiencia del mercado de forma débil. Las primas o los descuentos predicen los rendimientos netos de los activos, pero débilmente. Originalidad/valor: Los hallazgos apuntan a la idea de que el mercado de fondos cerrados es algo predecible e ineficiente (en su forma débil), ya que el mercado parece ser capaz de anticipar los rendimientos futuros de un fondo utilizando la información contenida en las primas (o descuentos). En particular, el mercado tiene la capacidad de anticipar el comportamiento futuro porque las primas crecientes pronostican rendimientos decrecientes del precio de las acciones para uno o dos períodos futuros.
Keywords: Closed-end fund; Discount; Fondo cerrado; Premium; Descuento; Puzzle; Premium; Puzzle; Vector autoregressive models; Modelos vectoriales autorregresivos; https://purl.org/pe-repo/ocde/ford#5.02.04